Degradation of the Oxirane Ring of Epoxidized Vegetable Oils with Hydrogen Peroxide Using an Ion Exchange Resin - Campanella, Alejandrina (2005)
The influence of different process variables (stirring, temperature, hydrogen peroxide concentration, particle diameter and amount of catalyst added) on the oxirane ring-opening reaction caused by hydrogen peroxide (H2O2) during the manufacture of epoxides obtained from triglycerides using a gel-type strong acid ion exchange resin, Amberlite IR-120, is analyzed. The degradation reaction with H2O2 is first-order with respect to the epoxide [kobs(70 ºC) = 3.37 ± 0.606 x 10 -4 min -1; Ea = 99.2 ± 1.3 kJ mol -1] and second-order with respect to H2O2, as expected, but only if moderate concentrations of peroxide are used. Highly concentrated H2O2 attacks the structure of the polymer and exposes free protons from the resin network. Ring opening increases either by adding a higher amount of catalyst to the system or by decreasing the particle size of the catalyst since, in both cases, the external area of the catalyst (i.e., available surface protons) becomes larger.